The work of habitus in naturalizing socially produced differences : a case study on an elite independent school in Singapore - Tan, Eunice Hui Ying (2017)
This paper seeks to uncover the underlying generative principles that guide the ways of thinking in an elite school in Singapore by illuminating how experiences matter in embodying privilege and how students, regardless of class backgrounds, have to remake themselves in schools in order to embody privilege of ease. Using Bourdieu’s concept on habitus, this study aims to understand how socially produced differences are naturalized as individuals’ aptitudes and effort, thus obscuring durable structural class inequalities within our meritocratic and inclusive society. This paper also aims to uncover the unequal affective aspects of class experiences within an elite school. This study is sociologically significant with its contribution in understanding how class cuts deeply into the formation of self, how privilege is learnt, embodied and naturalized, how schools naturalize hierarchies and the reproduction of institutionalized inequalities, and how class structure and its durabilities consequentially persist over time.